Adapted text benefits for teachers and students: A retroactive case study - Tucker, Lauren (Journal of Learning and Teaching in Digital Age, 2021)
This case study retrospectively reflects on a self-contained teacher’s decision to pair publisher-created adapted text with audio support as part of a multicomponent reading intervention. She evolved from creating her own adapted text to implementing publisher-created adapted text throughout a school year. The study analyzed students’ reading comprehension test scores throughout the year to examine the influence of publisher-created adapted text embedded within a multi-component reading intervention. The Related-Samples Wilcoxon Signed Rank Test revealed significance (p=.043) between students’ fall and spring Reading Inventory scores, with a moderate effect size (r=.562). The teacher made the instructional decision to implement publisher-created adapted text which eliminated time consuming self-adaptation of materials (Browder et al., 2007) and her students continued to make progress with this shift of materials with some demonstrating significant progress by the end of the school year.
Number: 1
Keywords: dept.sed